Clinical Profile and Outcome of Postthymectomy versus Non-Thymectomy Myasthenia Gravis Patients in the Philippine General Hospital: A 6-Year Retrospective Study - De Roxas, Ranhel C.; Bagnas, Marjorie Anne C.; Baldonado, Jobelle Joyce Anne R.; Rivera, Jonathan P.; Roxas, Artemio A. (Frontiers in Neurology, 2016)
Background: Myasthenia gravis is an autoimmune neuromuscular disorder characterized by the production of abnormal autoantibodies directed against the receptors present in the neuromuscular junction. It has been the standard practice to offer thymectomy in all generalized myasthenia gravis patients despite the lack of robust evidence. Objectives: The objectives of this study are to describe the clinical profile and differentiate the clinical outcomes of thymectomy versus non-thymectomy, and thymomatous versus nonthymomatous myasthenia gravis patients in the Philippine General Hospital. Methodology: Between 2009 and 2014, a total of 69 post-thymectomy and 16 nonthymectomy patient records were successfully retrieved. The demographic characteristics, surgical approach and histopathologic results were obtained. The clinical outcome after six months or one year follow-up was also determined and grouped according to the following: 1) complete remission, 2) pharmacological remission, 3) no clinical change 4) worsening symptoms and 5) mortality. Results: Majority of patients were females (68.0%) with a mean age of 39.8 years and a mean duration of myasthenic symptoms of 21 months. Using the MGFA classification, 54.1% of patients fell under Class II and 48.2% of them presented with generalized weakness. In this study, 60.8% of post-thymectomy myasthenia gravis patients had either complete remission or pharmacologic remission compared to 12.5% among non-thymectomy patients (p-value <0.001). No significant difference in the clinical outcome was found between thymomatous and non-thymomatous myasthenia gravis after thymectomy (p-value 0.29). Conclusion: This study showed that both thymomatous and non-thymomatous myasthenia gravis patients who underwent thymectomy had a higher incidence of complete stable remission and pharmacologic remission as compared to myasthenia gravis patients who did not undergo thymectomy. Keywords: myasthenia gravis, thymoma, non-thymomatous, thymectomy